2022
DOI: 10.1088/1361-6528/ac6c98
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic features of free-standing chitosan nanocomposite film with silver and graphene oxide for SERS applications

Abstract: A scalable procedure of SERS substrates design was developed using a novel plasmonic structure based on a freestanding chitosan film, silver nanoparticles, and graphene oxide. Chitosan provides a uniform distribution of silver nanoparticles from a colloidal suspension and, therefore, a reproducible Raman signal from local areas of measurements of several tens of microns. The addition of graphene oxide (GO) to the colloidal solution of silver nanoparticles suppresses the tortuous background fluorescence signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It was also reported that the graphene-modified SERS substrate is able to generate the SERS chemical enhancement effect [19,20]. An Ag/TiO 2 composite is suitable for SERS substrate application since both Ag and GO composites have SERS activity [21,22]. Our previous works had proven that GO modification of Ag/TiO 2 NTA could be used for SERS-sensing detection of organic aromatic ring molecules [23].…”
Section: Introductionmentioning
confidence: 97%
“…It was also reported that the graphene-modified SERS substrate is able to generate the SERS chemical enhancement effect [19,20]. An Ag/TiO 2 composite is suitable for SERS substrate application since both Ag and GO composites have SERS activity [21,22]. Our previous works had proven that GO modification of Ag/TiO 2 NTA could be used for SERS-sensing detection of organic aromatic ring molecules [23].…”
Section: Introductionmentioning
confidence: 97%
“…The details of composites, concentration of Ag loading, and LOD of MB reported in the literature and present work are compared and tabulated in Table in the Results and Discussion. Other substrates synthesized for SERS application with higher loadings of nanostructures were observed. ,, From the literature, it is observed that the loading of high concentrations of nanomaterials onto support materials results in enhanced performance. The use of high-concentration nanomaterials is not economical.…”
Section: Introductionmentioning
confidence: 98%
“…Other substrates synthesized for SERS application with higher loadings of nanostructures were observed. 22,24,25 From the literature, it is observed that the loading of high concentrations of nanomaterials onto support materials results in enhanced performance. The use of high-concentration nanomaterials is not economical.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the natural reed leaves, without any special pretreatment, coated by silver, have been utilized as a self-assembled plasmonic structure for ultra-sensitive crystal violet trace detection with sensitivity as low as 10 −13 M using a novel natural surface-enhanced fluorescence [ 2 ]. Recently, a scalable design of SERS substrate based on a biopolymer of free-standing chitosan film, silver nanoparticles, and graphene oxide has been demonstrated [ 3 ]. The developed plasmon hybrid structures were assessed by their SERS-sensitivity, reproducibility, stability, and quenching capability.…”
Section: Introductionmentioning
confidence: 99%